A cor púrpura : desvendando o processo de adaptação cinematográfica do romance epistolar - Dimitrov, Luciana Duenha (2015)
Adapting literature to movies has been constantly studied since the Seventh Art became a forming part of the Western Culture. However, adapting implies choices that may encumber the structures upon which the novel is established. The simple fact that the novel has to be shorten to a limited quantity of minutes presents, on its own, decisions that, most of the times, dissatisfies both audience and critics that await for, while at the film mode, an authentic reproduction of the literary piece. Deeply criticized, the adaptation of The Color Purple is to be studied at this work. Constructed as an epistolary novel, Alice Walker’s best seller was published in 1982 and adapted by Steven Spielberg in 1985. By analyzing these corpora, the main goal here is to unveil the adaptation mechanisms that were used in the transformation process from the book to the movie. In order to study the adaptation, theorists like George Bluestone, Linda Hutcheon, Siobhan O’Flynn, Cristian Metz, Sarah Kozloff are of urgent importance. Elizabeth H. Cook, Amanda Gilroy, W.M. Verhoeven, Linda Kauffman, Mary Favret are taken as essential names in order to comprehend the structure of the epistolary novel.